Protective Effects of Vitamin D3 on Male Rat’s Hepatic Cell Injured by Diclofenac, A Histopathological Study - Ali A. Tala’a (مجلة الانبار للعلوم البيطرية, 2022)
This experiment aimed to study the protective effects of vitamin D3 on hepatic cells injured by Diclofenac. Twenty-one male rats, 8 to 12 weeks of age and in weight from 180 to 220 grams, were housed in a standard, pathogen-free environment in the “College of Veterinary Medicine, University of Fallujah,” given unrestricted access to standard rat water and food. Then the rats were divided into 3 groups (each group containing 7 rats): G1 control group (IM injection of distill water for 7 days), G2 Diclofenac only (7-day course of a 10 mg/kg IM injection of diclofenac), G3 received intramuscular injections of VD3 three times per week at a dose of 1000 IU/Kg, then a 7-day course of a 10 mg/kg IM injection of diclofenac. Liver histological sections of the normal control (G1) showed no histopathological changes, while the histopathological sections of the liver of G2 exhibit hydropic degeneration, blood vessels congestion and inflammatory cell infiltration, Liver sections of G3 presented blood vessels congestion and mild inflammatory cell infiltration. This study concluded that VD3 can decrease the liver damage caused by diclofenac